DDIS-29. BRAIN-PENETRANT MICROTUBULE-TARGETING AGENT, ST-401, KILLS GLIOBLASTOMA THROUGH A NOVEL MECHANISM. (11th November 2019) - Horne, Eric; Xu, Cong; Vicente, Juan-Jesus; Cimino, P J; Wagenbach, Michael; Hamel, Ernest; Gussio, Rick; Diaz, Philippe; Uhlenbruck, Benjamin; Deckwerth, Thomas; Wordeman, Linda; Holland, Eric; et al.
Abstract: Glioblastomas are particularly sensitive to mitotic disruption when compared with nonmalignant cells and thus microtubule-targeting agents (MTA) represent promising therapeutics to treat patients with glioblastomas; but few such compounds pass the blood brain barrier. We developed a series of modified carbazoles, evaluated their anti-cancer activity in glioblastoma cells in culture and identified ST-401 as the most potent compound (IC50, 10 – 102 nM, depending on the cell line). Testing of ST-401 on the NCI 60 cancer cell panel indicated that its anti-tumor activity does not correlate with any of the compounds tested thus far through this platform but showed weak correlations for taxol (p=0.46) and vinblastine (p=0.34). Thus, ST-401 may kill cancer cells through a novel mechanism related to disruption of MT function. Biochemical analysis indicates that ST-401 binds to the colchicine site of tubulin and inhibits tubulin assembly. Real-time imaging of MT dynamics in cells in culture shows that ST-401 reduces MT assembly rates but in a reversible fashion. ST-401 potently blocks mitotic progression and triggers cell death in multiple glioblastoma lines in culture, including patient-derived glioblastomas of the proneural, mesenchymal and classical subtypes. We established the maximum tolerated dose (MTD) of ST-401 in mice (20 mg/kg/bdip) and found that its acute i.p. injection results in micromolar amounts of ST-401 in mouse brain. Using this treatment regimen, we found that ST-401 reduces tumor growth and doubles overall survival in a human tumor xenograft mouse model system. ST-401 also increases by 2-fold overall survival in the genetic RCAS-PDGF glioblastomas mouse model treated with standard care (radiation and Temodar® treatments). Histological analysis of RCAS-PDGF glioblastoma tissue shows that ST-401 triggers mitotic arrest of glioblastoma cells. ST-401 represents a promising lead compound for the treatments for patients diagnosed with glioblastomas.